Moderasi Beragama dalam Pembentukan Karakter Santri Yayasan Ar-Rahmani - As'ad, As'ad; As'ad; Fatimah; Ananto , Irfan (PT. Lancar Media Komunikasi, 2025)
The purpose of this research is to instill moderate religious values (wasathiyah) of mutual respect and to create religious harmony and character building (ahlaqul karimah) for students at the Ar- Rahmani Foundation, Ciputat District, South Tangerang. This research uses a qualitative approach and the method used is a case study that aims to capture events, facts, data, and incidents regarding curriculum management at the school. The data sources and respondents of the study are the religious division of the Ar-Rahmani Foundation as key informants (main sources) and all teachers of the Ar-Rahmani Foundation, Ciputat, South Tangerang City. The data collection techniques and procedures are carried out by means of in-depth interviews, observations or observations of researchers in field activities, and document analysis related to the object of this research. The research results can be concluded that there are three steps in realizing religious moderation at the Ar-Rahmani Foundation: 1) the curriculum refers to the Indonesian Ministry of Religious Affairs and Rabitah Maahid Islamiyah (RMI), 2) students are taught tolerance in different understandings, 3) humanistic values or ukhuwah are highly respected (ahlakul karimah). The need to strengthen religious moderation is to form a moderate, non-exclusive religious understanding and respect for diversity in order to create a harmonious life.